Analysis of Stress Ratio and Stress Regime in West Java - Sirait, Anne M.; Palgunadi, Kadek Hendrawan; Simanjuntak, Andrean V. H.; Rahmania, Nadhira; Naufal, Izaaz; Dhiarofa, Muhammad Nanda Rizqi; Karimah, Akhlaqul; Al-Ghifari, Rafi Sadam; Ramadhani, Azhari; Hady, Farrastha Hady; Warnana, Dwa Desa; Suryanto, Wiwit (Indonesian Journal on Geoscience, 2026)
This study actively investigates stress ratios, principal stress orientations, and stress regimes in the West Java Province, Indonesia, by simultaneously inverting both the stress tensor and fault orientations from 232 moment tensors. It identifies diverse stress regimes, including normal and reverse faulting in the subduction zone, as well as mixed reverse and strike-slip faults across the island. Stress ratios range from 0.08 to 0.97. Sedimentary basins in the northeast produce lower values, while tectonic forces near the southern subduction zones generate higher values. In the subduction zone, plate bending generates normal faulting, while compressional forces lead to reverse faulting. The fore-arc region exhibits a variety of regimes: normal, reverse, and strike-slip, indicating transitions in the dynamics of subduction. Across the island, a combination of reverse and strike-slip faulting suggests crustal compression, with Mount Anak Krakatau exhibiting evidence of normal faulting. The study uncovers a complex interplay of subduction processes, crustal deformation, and geological heterogeneities. It outlines stress regimes ranging from normal and reverse faulting in the subduction zone to mixed reverse and strike-slip faulting on the island. These findings offer crucial insights into the tectonic processes shaping West Java, and lay the groundwork for more informed seismic hazard assessments and risk mitigation strategies.